2011
DOI: 10.1186/1532-429x-13-67
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of late gadolinium enhancement in Takotsubo cardiomyopathy: serial analysis of cardiovascular magnetic resonance images

Abstract: BackgroundOur study aimed to investigate both the clinical implications of late gadolinium enhancement (LGE) by cardiovascular magnetic resonance (CMR) and the relation of LGE to clinical findings in patients with Takotsubo cardiomyopathy (TTC).MethodsWe evaluated 20 consecutive patients (2 men, 18 women; median age, 77 years; interquartile range [IQR] 67-82 years) who were admitted to our hospital with the diagnosis of TTC. CMR was performed within 1 week after admission, and follow-up studies were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 24 publications
0
72
0
1
Order By: Relevance
“…Focal late gadolinium enhancement in cardiac magnetic resonance, which is believed to be evidence of irreversible fibrosis, is observed in 9-40% of patients with TTC [24][25][26][27]. Cardiac rupture is the most severe and oftentimes fatal complication of TTC, which supports the transmyocardial damage [28,29].…”
mentioning
confidence: 79%
“…Focal late gadolinium enhancement in cardiac magnetic resonance, which is believed to be evidence of irreversible fibrosis, is observed in 9-40% of patients with TTC [24][25][26][27]. Cardiac rupture is the most severe and oftentimes fatal complication of TTC, which supports the transmyocardial damage [28,29].…”
mentioning
confidence: 79%
“…9 -14 Interestingly, Naruse and colleagues recently observed a relation between time to ECG normalization and LGE among patients with Takotsubo cardiomyopathy as well. 30 Third, none of the patients included in the present study developed pathologic Q waves. Moon et al have shown that the presence of Q wave in ischemic heart disease is mainly related to the extent of infarct size and, secondarily, to its transmural extent 31 ; accordingly, the scattered nature and the absence of transmurality of myocardial damage in AM may explain the lack of development of Q waves in this group of patients.…”
Section: Electrocardiography In Infarct-like Myocarditis and Relationmentioning
confidence: 75%
“…However, the signal intensity of LGE was lower than that Fig. 3 a Four-chamber view showing mid-apical oedema in T2-weighted sequences and b no evidence of significant late gadolinium enhancement in T1-weighted inversion recovery post-contrast sequences usually documented in cases of MI or myocarditis [21]. Whilst initially it was believed that lack of LGE was a necessary condition to diagnose TCM and would thus help differentiate it from MI, in the study by Haghi et al [22], 88 % of patients showed a patchy type of LGE.…”
Section: Cmr Findings In Tcmmentioning
confidence: 88%